Method for evaluating the uniformity of the coating layer and silver-coated copper powder

JP2026166665APending Publication Date: 2026-10-14MITSUI MINING & SMELTING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059751
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、コア粒子の表面に被覆層及び表面処理層を有する銀被覆銅粉において、被覆層の均一性を簡便に評価する方法が提供される。また本発明によれば、均一な被覆層を有する前記銀被覆銅粉が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166665000002
    Figure 2026166665000002
  • Figure 2026166665000003
    Figure 2026166665000003
  • Figure 2026166665000004
    Figure 2026166665000004
Patent Text Reader

Abstract

To provide a method for easily evaluating the uniformity of a coating layer in silver-coated copper powder having a coating layer and a surface treatment layer on the surface of core particles, and to provide silver-coated copper powder having a uniform coating layer. [Solution] An observation area for excitation laser light is defined on the silver-coated copper powder, and multiple irradiation areas are provided within the observation area, where excitation laser light of a wavelength absorbable by the silver element is irradiated. By irradiating each of the irradiation areas with the laser light, the Raman spectrum of the silver-coated copper powder is obtained for each irradiation area. Multiple normalized Raman spectra are obtained by normalizing each of the Raman spectra with respect to the peak intensity of a reference peak. One wavenumber of the peak originating from the surface treatment agent observed in the multiple normalized Raman spectra is selected, and the uniformity of the coating layer is evaluated based on the ratio of the number of irradiation areas where the intensity of the normalized Raman spectrum at the wavenumber is above a threshold to the total number of irradiation areas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for evaluating the uniformity of a coating layer in silver-coated copper powder having a coating layer and a surface treatment layer on the surface of core particles. The present invention also relates to silver-coated copper powder.

Background Art

[0002] Silver is used as a wiring material and a bonding material for electronic components, and as electronic components have become more advanced in function year by year, the demand for lower prices of these materials has also increased. Silver wiring and silver bonding materials are usually produced by a method of sintering silver powder contained in a paste. In particular, the reason why silver powder is used for wiring materials with high consumption is that excellent properties such as high oxidation resistance and high conductivity can be obtained when forming wiring by sintering in air, but since silver is expensive, alternative materials have been sought. From such a viewpoint, development of low-cost silver-coated copper powder has been advanced in recent years.

[0003] For example, Patent Document 1 proposes a powder of metal particles having metal core particles with a copper content of 80% by mass or more and a silver coating layer covering the metal core particles. The document describes that the powder can form a highly conductive conductive film when used as a conductive filler, and has high performance of suppressing the temporal change in conductivity of the conductive film.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of Invention

Problems to be Solved by the Invention

[0005] Incidentally, a factor affecting the properties of silver-coated copper powder is the uniformity of the silver coating. However, a method for easily evaluating the uniformity of the silver coating has not been proposed so far. Furthermore, the silver-coated copper powder described in Patent Document 1 had considerable room for improvement in the uniformity of the silver coating.

[0006] Therefore, the object of the present invention is to provide a method for easily evaluating the uniformity of a coating layer in silver-coated copper powder having a coating layer and a surface treatment layer on the surface of core particles, and to provide silver-coated copper powder having a uniform coating layer. [Means for solving the problem]

[0007] Copper-containing core particles, Displaced on the surface of the core particles, a coating layer containing silver, Displaced on the surface of the coating layer, a surface treatment layer containing a surface treatment agent, A method for evaluating the uniformity of the coating layer in silver-coated copper powder containing the following: An observation area is defined in the silver-coated copper powder, and multiple irradiation areas are provided within the observation area to irradiate it with excitation laser light of a wavelength absorbable by the silver element. By irradiating each of the irradiation regions with the laser light, the Raman spectrum of the silver-coated copper powder is obtained for each irradiation region. By normalizing each of the Raman spectra obtained for each irradiation region with respect to the peak intensity of a reference peak derived from copper oxide, multiple normalized Raman spectra are obtained. One wavenumber of the peak originating from the surface treatment agent observed in the above-mentioned multiple normalized Raman spectra is selected, The ratio n / N of the number of irradiation regions where the intensity of the normalized Raman spectrum at the wavenumber is above a threshold is calculated relative to the total number N of irradiation regions. This invention provides a method for evaluating the uniformity of a coating layer, which evaluates the uniformity of the coating layer based on the aforementioned ratio.

[0008] Furthermore, the present invention relates to core particles containing copper, Displaced on the surface of the core particles, a coating layer containing silver, Displaced on the surface of the coating layer, a surface treatment layer containing a surface treatment agent, A silver-coated copper powder containing the same, wherein the ratio n / N of n to N calculated by the following method is 0.05 or more, is provided as the silver-coated copper powder. <Method for calculating n / N> An observation region is defined on the silver-coated copper powder, and a plurality of irradiation regions to be irradiated with an excitation laser beam having a wavelength of 532 nm are provided in the observation region, By irradiating each of the irradiation regions with the laser beam, a Raman spectrum of the silver-coated copper powder is obtained for each of the irradiation regions, Each of the Raman spectra obtained for each of the irradiation regions is processed at 245cm -1 to 255cm -1 By normalizing with respect to the peak intensity of a reference peak observed at the following wavenumbers, a plurality of normalized Raman spectra are obtained, One wavenumber of the peak derived from the surface treatment agent, which is observed in the plurality of normalized Raman spectra, is selected, The number n of the irradiation regions where the intensity of the normalized Raman spectrum at the wavenumber is 10 times or more the peak intensity of the reference peak is determined, The ratio n / N of n to the total number N of the irradiation regions is calculated.

[0009] Further, the present invention relates to core particles containing copper, and a coating layer disposed on the surface of the core particles and containing silver, A silver-coated copper powder comprising the above, wherein the ratio n / N of n to N calculated by the following method is 0.05 or more, is provided as the silver-coated copper powder. <Method for calculating n / N> A surface treatment layer containing a surface treatment agent is formed on the surface of the coating layer, An observation region is defined on the silver-coated copper powder, and a plurality of irradiation regions to be irradiated with an excitation laser beam having a wavelength of 532 nm are provided in the observation region, By irradiating each of the irradiation regions with the laser beam, a Raman spectrum of the silver-coated copper powder is obtained for each of the irradiation regions, Each of the Raman spectra obtained for each of the irradiation regions is processed at 245cm -1 to 255cm -1By normalizing the peak intensity of the reference peak observed at the following wavenumbers, multiple normalized Raman spectra are obtained. One wavenumber of the peak originating from the surface treatment agent observed in the above-mentioned multiple normalized Raman spectra is selected, The number n of irradiation regions is determined such that the intensity of the normalized Raman spectrum at the wavenumber is 10 times or more the peak intensity of the reference peak. Calculate the ratio n / N to the total number N of irradiation regions. [Effects of the Invention]

[0010] According to the present invention, a method for easily evaluating the uniformity of the coating layer in silver-coated copper powder having a coating layer and a surface treatment layer on the surface of core particles is provided. Furthermore, according to the present invention, the silver-coated copper powder having a uniform coating layer is provided. [Brief explanation of the drawing]

[0011] [Figure 1] Figure 1 shows the electric field generated when silver-coated copper powder is irradiated with laser light. [Figure 2] Figure 2 shows the Raman scattering from a surface treatment agent present on the surface of silver-coated copper powder. [Figure 3] Figure 3 shows surface-enhanced Raman scattering from a surface treatment agent present in a region adjacent to two silver-coated copper powders. [Modes for carrying out the invention]

[0012] The present invention will be described below based on its preferred embodiments. First, the evaluation method of the present invention will be described. The evaluation method of the present invention relates to a method for evaluating the uniformity of a coating layer in silver-coated copper powder, which comprises copper-containing core particles, a silver-containing coating layer disposed on the surface of the core particles, and a surface treatment layer disposed on the surface of the coating layer and containing a surface treatment agent. Details of the silver-coated copper powder to be evaluated will be described later.

[0013] The principle of the evaluation method of the present invention is as follows (Figures 1 to 3). When laser light 1 of a wavelength absorbable by the silver coating layer is irradiated onto silver-coated copper powder 2, an electric field 3 is generated on the surface of the silver-coated copper powder 2 due to surface plasmon resonance (Figure 1). If a surface treatment agent is present in the electric field 3 thus generated, enhanced Raman scattering 4 of the surface treatment agent is observed due to the electric field 3 (surface-enhanced Raman scattering) (Figure 2). In particular, when two silver-coated copper powders 2,2 are close together, irradiating them with laser light 1 enhances the generated electric field 3 in the region 5 adjacent to both silver coating layers of the two silver-coated copper powders 2,2 (Figure 3). Therefore, if a surface treatment agent is present in region 5, significantly enhanced Raman scattering 6 is observed. The following describes a method for evaluating the uniformity of the coating layer using the surface-enhanced Raman scattering method described above.

[0014] [Method for evaluating the uniformity of the coating layer] The method for evaluating the uniformity of the coating layer of the present invention comprises the following steps 1 to 3 in this order. 1. Step to obtain the Raman spectrum of silver-coated copper powder (Raman spectrum acquisition step). 2. A step of obtaining multiple normalized Raman spectra by normalizing the Raman spectrum with respect to the peak intensity of a reference peak (normalized Raman spectrum acquisition step). 3. A step to evaluate the uniformity of the coating layer using the normalized Raman spectrum (evaluation step of the uniformity of the coating layer).

[0015] 1. Steps to acquire Raman spectra In this step, first, prepare the silver-coated copper powder that will be used as the measurement sample. The amount of silver-coated copper powder used is not particularly limited, as long as it is enough to cover the entire observation area described later.

[0016] Next, the observation area of ​​the silver-coated copper powder is defined. The observation area may be set within the outer shape of one particle constituting the silver-coated copper powder, or it may be set to span two or more such particles. There are no restrictions on the shape of the observation area; it may be a polygon or other shape enclosed by straight lines, or a circle or ellipse or other shape enclosed by curves. It may also be a shape enclosed by a combination of both straight lines and curves. In particular, a rectangular shape for the observation area is preferable because it makes it easier to set the irradiation area, as described later. The aforementioned "shape of the observation area" refers to the shape of the observation area as observed in a plan view of the silver-coated copper powder, viewed from a direction aligned with the irradiation direction of the excitation laser light.

[0017] Once the observation area is defined, multiple irradiation areas are then created within the observation area to irradiate it with excitation laser light. The irradiation areas should be set up so that they do not overlap. Each irradiation area may be adjacent to another or separated by a distance. There are no particular restrictions on the shape of the irradiation areas, but they may be circular or polygonal, for example. There are also no particular restrictions on the area of ​​the irradiation areas, but from the viewpoint of improving the accuracy of evaluating the uniformity of the coating layer, it is preferable that each irradiation area has the same area. From the viewpoint of ensuring a sufficient number of irradiation areas and improving the accuracy of evaluating the uniformity of the coating layer, it is preferable to provide 100 or more irradiation areas, more preferably 225 or more, and even more preferably 400 or more. There is no particular upper limit on the number of irradiation areas, but from the viewpoint of shortening the measurement time, it is preferable to provide 900 or fewer irradiation areas, more preferably 625 or fewer, and even more preferably 400 or fewer.

[0018] From the viewpoint of improving the accuracy of evaluating the uniformity of the coating layer, it is preferable that the area of ​​each irradiation region be appropriately determined according to the particle size of the silver-coated copper powder being measured. More specifically, the area of ​​each irradiation region is preferably 0.005 times or more and 10 times or less the average particle size of the silver-coated copper powder, more preferably 0.01 times or more and 1 time or less, and even more preferably 0.1 times or more and 0.3 times or less. In this specification, the average particle diameter refers to the cumulative particle size D at 50% of the cumulative volume, as measured by laser diffraction scattering particle size distribution analysis. 50 That is the matter. In particular, when the average particle diameter of the silver-coated copper powder is 1 μm or more and 10 μm or less, the area of each irradiation region is each independently 0.5 μm 2 or more and 8 μm 2 or less, preferably 0.5 μm 2 or more and 4.5 μm 2 or less, more preferably 0.5 μm 2 or more and 2 μm 2 or less, still more preferable.

[0019] The area of the observation region may be appropriately set according to the number of the irradiation regions described above and the area of each irradiation region. For example, when the average particle diameter of the silver-coated copper powder as the measurement object is 0.1 μm or more and 10 μm or less, the area of the observation region is preferably 100 μm 2 or more, more preferably 225 μm 2 or more, still more preferably 400 μm 2 or more. The area of the observation region is preferably 14400 μm 2 or less, more preferably 5625 μm 2 or less, still more preferably 1600 μm 2 or less, and particularly preferably 900 μm 2 or less. The "area of the observation region" refers to the area of the irradiation region observed in a plan view of the silver-coated copper powder as viewed from a direction along the irradiation direction of the excitation laser beam.

[0020] As a specific example of the method of providing the plurality of irradiation regions in the observation region, a method of providing the plurality of irradiation regions in a lattice form in the observation region can be mentioned. In this case, it is preferable that the respective irradiation regions are arranged intermittently in a first direction and a second direction orthogonal to the first direction. Alternatively, the irradiation regions can also be set by dividing the observation region into a lattice form by a plurality of first division straight lines parallel to each other and second division straight lines intersecting the first division straight lines (the second division straight lines are parallel to each other). In this case, the first division straight line and the second division straight line are preferably orthogonal to each other.

[0021] Next, the irradiation area is irradiated with excitation laser light. The excitation laser light is typically monochromatic. The wavelength of the excitation laser light can be any wavelength that can be absorbed by the silver element present in the coating layer of the silver-coated copper powder, for example, it can be between 325 nm and 1064 nm. In particular, because absorption by the silver element is strong, the wavelength of the excitation laser light is preferably between 325 nm and 800 nm, and more preferably between 325 nm and 600 nm.

[0022] The laser light source is not particularly limited as long as it can emit laser light of the desired wavelength, and examples include YAG lasers, YVO4 lasers, fiber lasers, LD lasers (semiconductor lasers), etc.

[0023] The output of the excitation laser light is preferably such that it does not alter the silver-coated copper powder and does not saturate the detector. From this viewpoint, for example, when using an excitation laser light with a wavelength of 532 nm, the output of the laser light is preferably 0.5 mW or less, more preferably 0.3 mW or less, and even more preferably 0.2 mW or less. Furthermore, from the viewpoint of shortening the measurement time, the laser light output is preferably 0.01 mW or more, more preferably 0.05 mW or more, even more preferably 0.075 mW or more, and particularly preferably 0.1 mW or more. The irradiation time of the excitation laser light should be appropriately adjusted considering the output of the laser light as described above, but from the viewpoint of improving the accuracy of evaluating the uniformity of the coating layer, it is preferably 1 second or more, more preferably 5 seconds or more, and even more preferably 10 seconds or more. There is no particular upper limit on the irradiation time of the excitation laser light, but from the viewpoint of shortening the measurement time, it can be set to, for example, 60 seconds or less, 30 seconds or less, or 20 seconds or less.

[0024] After irradiating the silver-coated copper powder with excitation laser light as described above, the Raman spectrum of the silver-coated copper powder is obtained. To obtain the Raman spectrum, the scattered light (Rayleigh scattered light and Raman scattered light) generated by the irradiation of the excitation laser light is passed through a filter to remove the Rayleigh scattered light and obtain the Raman scattered light, which is then decomposed into a spectrum by a spectrometer and detected by a detector.

[0025] In this evaluation method, the Raman spectrum is acquired for each irradiated area. Specifically, the first irradiated area is irradiated with excitation laser light for a predetermined time, and the Raman spectrum at that time is acquired. Next, the second irradiated area is irradiated with excitation laser light for a predetermined time, and the Raman spectrum at that time is acquired. This is repeated to acquire the Raman spectrum for all irradiated areas.

[0026] 2. Steps for obtaining a normalized Raman spectrum After obtaining Raman spectra of silver-coated copper powder for each irradiation region, these Raman spectra are then normalized with respect to the peak intensity of a reference peak to obtain multiple (i.e., for each irradiation region) normalized Raman spectra. The aforementioned "normalization" refers to rescaling the Raman spectrum so that the peak intensity of the reference peak becomes a specific value. For example, by dividing the signal intensity of the Raman spectrum by the peak intensity of the reference peak, a normalized Raman spectrum with a reference peak intensity of "1" can be obtained. Alternatively, normalization may be performed by dividing the signal intensity of the Raman spectrum by half the peak intensity of the reference peak so that the peak intensity of the reference peak becomes "2". In either case, it is preferable to perform normalization so that the peak intensity of the reference peak is the same value in all normalized Raman spectra.

[0027] In the Raman spectrum of silver-coated copper powder, typically, copper oxide (CuO xA peak originating from (where x represents a number between 1 and 2) is observed. Therefore, it is preferable to use this copper oxide-derived peak as the reference peak. This copper oxide-derived peak is observed at 245 cm⁻¹. -1 Over 255cm -1 It is preferable to use the peak observed at the following wavenumber: 245 cm⁻¹. -1 Over 255cm -1 The peaks observed at the following wavenumbers have sufficiently high peak intensities and often do not overlap with other peaks, making them suitable for use as reference peaks.

[0028] 3. Steps for evaluating the uniformity of the coating layer In this step, the uniformity of the coating layer is evaluated using multiple normalized Raman spectra obtained in the previous step. First, one wavenumber of a peak originating from the surface treatment agent is selected from multiple normalized Raman spectra. The wavenumber of the "peak originating from the surface treatment agent" depends on the type of surface treatment agent contained in the surface treatment layer. For example, if the surface treatment agent contains fatty acids such as stearic acid, the wavenumber of the peak originating from the surface treatment agent is 1000 cm². -1 More than 2000cm -1 It is preferable to select the wavenumber of the peak observed below, which is 1100 cm. -1 More than 1900cm -1 It is more preferable to select the wavenumber of the peak observed below, which is 1300 cm. -1 More than 1800cm -1 It is even more preferable to select the wavenumber of the peaks observed below. More specifically, as the wavenumber of the peaks derived from fatty acids, for example, 1580 ± 5 cm². -1 or 1395±5cm -1 You can choose this option. Furthermore, if the surface treatment agent contains azole compounds such as benzotriazole, the wavenumber of the peak originating from the surface treatment agent should be 500 cm². -1 More than 2000cm -1 It is preferable to select the wavenumber of the peak observed below, which is 1000 cm. -1 More than 2000cm-1 It is more preferable to select the wavenumber of the peak observed below, which is 1200 cm. -1 More than 1800cm -1 It is even more preferable to select the wavenumber of the peak observed below. More specifically, the wavenumber of the peak derived from the azole compound, for example, 1390 ± 3 cm⁻¹. -1 or 1575±5cm -1 You can choose this option.

[0029] Next, the ratio n / N of the number of irradiated areas where the intensity of the normalized Raman spectrum at the selected wavenumber is above a threshold is calculated relative to the total number N of irradiated areas, and the uniformity of the coating layer is evaluated based on this ratio n / N. In order to properly evaluate the uniformity of the coating layer, it is preferable to appropriately set the threshold according to the type of surface treatment agent and the wavelength of the excitation laser light. For example, if the excitation laser light wavelength is 532 nm and the surface treatment agent contains stearic acid or benzotriazole, it is preferable that the threshold is 10 times or more the peak intensity of the reference peak in the normalized spectrum. There is no particular upper limit to the threshold, but for example, it can be 1000 times or less the peak intensity of the reference peak in the normalized spectrum.

[0030] A large ratio n / N indicates that the region 5 where the enhanced electric field 3 is generated, as shown in Figure 1(b), is uniformly present on the surface of the silver-coated copper particles. Therefore, the uniformity of the coating layer in the silver-coated copper particles can be evaluated based on the magnitude of the ratio n / N. In other words, the closer n / N is to 1, the higher the uniformity of the coating layer can be evaluated. In this specification, "uniformity of the coating layer" refers to the degree to which the surface of the core particles is covered by the coating layer. Therefore, "uniformity of the coating layer" does not include uniformity of the thickness of the coating layer.

[0031] [Silver coated copper powder] Next, the details of the silver-coated copper powder to be evaluated in the evaluation method of the present invention will be described. As described above, the silver-coated copper powder comprises core particles containing copper, a coating layer containing silver disposed on the surface of the core particles, and a surface treatment layer containing a surface treatment agent disposed on the surface of the coating layer. In this specification, "silver-coated copper powder" may refer to the individual particles constituting the silver-coated copper powder, or to the powder as an aggregate of such particles, depending on the context.

[0032] The copper content in the core particles is not particularly limited, but it is preferable, for example, to have 50% by mass or more, or 70% by mass or more, and especially 90% by mass or more, because the aforementioned reference peak is observed with high intensity. There is no particular upper limit to the copper content; for example, the core particles may consist only of copper and unavoidable impurities. The copper content in the core particles can be measured, for example, by ICP emission spectroscopy.

[0033] The silver-containing coating layer may be located on a portion of the core surface or on the entire surface of the core. From the viewpoint of being able to observe surface-enhanced Raman scattering with sufficiently high intensity, the silver content in the silver-coated copper powder is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more. The silver content in the silver-coated copper powder can be measured, for example, by ICP emission spectroscopy.

[0034] The surface treatment agent contained in the surface treatment layer is not particularly limited as long as surface-enhanced Raman scattering is observed with sufficient intensity, but it is preferably an organic surface treatment agent. Examples of organic surface treatment agents include fatty acids and their salts, azole compounds and their derivatives, surfactants, organometallic compounds, chelating agents, and polymer dispersants. Among these, it is more preferable that the surface treatment agent be one or more selected from the group consisting of fatty acids and their salts, and azole compounds and their derivatives.

[0035] Examples of the aforementioned fatty acids include saturated fatty acids such as stearic acid and lauric acid, and unsaturated fatty acids such as oleic acid and ricinoleic acid. Examples of the aforementioned azole compounds include triazole compounds such as triazole, benzotriazole, and 2H-triazole-5-carboxylic acid; and thiazole compounds such as thiazole and benzothiazole.

[0036] From the viewpoint of successfully evaluating the uniformity of the coating layer using the evaluation method described above, the content of the surface treatment agent in the silver-coated copper powder is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.02% by mass or more, relative to the amount of carbon element contained in the surface treatment agent, relative to the silver-coated copper powder. The method for measuring the content of surface treatment agents in silver-coated copper powder will be explained in the examples described later.

[0037] The average particle size of the silver-coated copper powder is not particularly limited, but is preferably 1.0 μm or larger, more preferably 1.2 μm or larger, even more preferably 1.5 μm or larger, even more preferably 2.0 μm or larger, and especially preferably 2.5 μm or larger. Similarly, the average particle size of the silver-coated copper powder is preferably 10.0 μm or smaller, more preferably 8.5 μm or smaller, even more preferably 8.0 μm or smaller, even more preferably 7.5 μm or smaller, and especially preferably 7.0 μm or smaller.

[0038] The BET specific surface area (SSA) of silver-plated copper powder is not particularly limited, but an SSA of 0.08 m² is not particularly limited. 2 It is preferable that the value be 0.10 m or more, and more preferably 0.10 m 2 It is 0.14m or more, and more preferably 0.14m 2 It is 0.17m or more, and more preferably 0.17m 2 It is 1 / g or more, and particularly preferably 0.20m 2 It is 1 / g or more. Similarly, the BET specific surface area SSA of silver-plated copper powder is 1.50 m². 2 It is preferable that it be less than or equal to / g, and more preferably 1.40m 2It is less than or equal to / g, and more preferably 1.30m 2 It is less than or equal to / g, and more preferably 1.00m 2 It is less than / g and 0.70m 2 It is less than / g.

[0039] The shape of the silver-coated copper powder does not necessarily have to be spherical; it can be any shape, such as flattened, polygonal, or uneven.

[0040] The silver-coated copper powder of the present invention exhibits improved oxidation resistance, and the degree of this oxidation resistance can be evaluated by the oxygen elevation rate. Specifically, from the viewpoint of ensuring that the oxidation resistance of the silver-coated copper powder and the conductive resin composition containing it is sufficiently improved, the oxygen elevation rate of the silver-coated copper powder is preferably 150.0% or less, more preferably 140.0% or less, and even more preferably 130.0% or less. From the viewpoint of making the above-mentioned advantages even more pronounced, a lower oxygen elevation rate is preferable, but it may also be 35.0% or more. The method for measuring the oxygen elevation rate of silver-coated copper powder will be explained in the examples described later.

[0041] Next, we will describe in detail the silver-coated copper powder that is particularly preferred among the silver-coated copper powders mentioned above (hereinafter also referred to as "the silver-coated copper powder of the present invention"). The silver-coated copper powder of the present invention is characterized by high uniformity of the coating layer. The uniformity of the coating layer in the silver-coated copper powder of the present invention can be evaluated by the evaluation method described above. More specifically, the ratio n / N calculated by the evaluation method described above is preferably 0.05 or higher, more preferably 0.15 or higher, and even more preferably 0.20 or higher. The ratio n / N in the silver-coated copper powder of the present invention shall be calculated based on the measurement results under the following measurement conditions.

[0042] <Measurement conditions> • Wavelength of excitation laser light: 532nm • Excitation laser output: 0.13mW • Irradiation time of excitation laser light: 10 seconds • Reference peak: 245cm -1 Over 255cm -1 Peaks originating from copper oxides are observed at the following wavenumbers. • Threshold: 10 times the peak intensity of the reference peak Other measurement conditions will be explained in the examples below.

[0043] The silver-coated copper powder of the present invention may not have a surface treatment layer. In this case, before evaluating the uniformity of the coating layer using the evaluation method described above, the silver-coated copper powder is treated with a surface treatment agent to form a surface treatment layer containing the surface treatment agent on the surface of the coating layer. The method for forming the surface treatment layer will be described later. In this case, it is preferable to use stearic acid or benzotriazole as the surface treatment agent for silver-coated copper powder, and it is more preferable to use stearic acid. The wavenumber of the peak derived from the surface treatment agent in the evaluation method described above is 1580 ± 5 cm² when the surface treatment agent is stearic acid. -1 If the surface treatment agent is benzotriazole, then 1390±3cm -1 It is preferable to adopt this approach.

[0044] Next, a preferred method for producing the silver-coated copper powder of the present invention will be described. This production method comprises the steps of obtaining silver-coated copper particles and applying a surface treatment agent to the surface of the silver-coated copper particles. The step of obtaining the silver-coated copper particles comprises the step of adding a complexing agent to a dispersion liquid, which will be described later, in at least two separate steps.

[0045] First, core particles are prepared. The core particles are made of copper. The shape of the core particles can be spherical, flattened, polygonal, spindle-shaped, or irregular. From the viewpoint of improving the oxidation resistance of the target silver-coated copper powder, it is preferable to use spherical core particles.

[0046] It is preferable to use core particles whose physical properties are within a predetermined range, as this allows for the successful acquisition of silver-coated copper powder whose physical properties, such as average particle diameter and BET specific surface area (SSA), are within the aforementioned range.

[0047] From the above viewpoint, it is preferable to use core particles with an average particle diameter of 0.9 μm or more, more preferably 1.1 μm or more, even more preferably 1.4 μm or more, even more preferably 1.9 μm or more, and particularly preferably 2.4 μm or more. From a similar viewpoint, it is preferable to use core particles with an average particle diameter of 9.9 μm or less, more preferably 8.4 μm or less, even more preferably 7.9 μm or less, even more preferably 7.4 μm or less, and particularly preferably 6.9 μm or less.

[0048] Regarding the BET specific surface area (SSA) of the core particle, from the perspective described above, it is 0.08 m². 2 It is preferable to use core particles of 0.10 m or more, and more preferably 0.10 m 2 It is 0.14m or more, and more preferably 0.14m 2 It is 0.17m or more, and more preferably 0.17m 2 It is 1 / g or more, and particularly preferably 0.20m 2 It is 1 / g or more. From a similar perspective, the BET specific surface area SSA is 1.50m². 2 It is preferable to use core particles of 1.40 m or less, and more preferably 1.40 m 2 It is less than or equal to / g, and more preferably 1.30m 2 It is less than or equal to / g, and more preferably 1.00m 2 It is less than / g and 0.70m 2 It is less than / g.

[0049] Core particles having such physical properties can be obtained, for example, by atomization methods such as gas atomization and water atomization, as well as by plasma methods. Alternatively, they can be easily obtained by a wet reduction method in which copper hydroxide is precipitated by reacting an aqueous copper salt solution with an alkaline agent, this copper hydroxide is first reduced to cuprous oxide in liquid, and the cuprous oxide is secondarily reduced to metallic copper in liquid. From the viewpoint of successfully obtaining silver-coated copper powder with an average particle diameter and BET specific surface area (SSA) within the above range, it is preferable to use core particles containing a large amount of spherical copper obtained by atomization.

[0050] Once the core particles are prepared, they may be subjected to surface treatment as needed. In this embodiment, for example, the surface of the core particles can be treated by depositing an acid or hydrazine onto it. This removes the oxide film on the surface of the core particles, allowing a silver coating layer to be successfully formed on the surface of the core particles.

[0051] Next, a dispersion is prepared. The dispersion can be prepared by dispersing the core particles in water. There are no particular restrictions on the method of mixing the core particles with water. For example, one method is to stir the water and then add the core particles to it and mix them.

[0052] From the viewpoint of successfully obtaining silver-coated copper powder, the content of core particles in the dispersion is preferably adjusted to 30 g / L or more, more preferably 40 g / L or more, even more preferably 50 g / L or more, even more preferably 70 g / L or more, and particularly preferably 85 g / L or more. From a similar viewpoint, the content of core particles in the dispersion is preferably adjusted to 300 g / L or less, more preferably 280 g / L or less, even more preferably 250 g / L or less, and even more preferably 220 g / L or less.

[0053] Once the dispersion is prepared, a silver coating layer is formed on at least a portion of the surface of the core particles. Methods for forming the silver coating layer include displacement plating, which utilizes the displacement reaction between copper and silver due to differences in ionization tendencies, and reduction, which uses a reducing agent. When placing the silver coating layer on the surface of the core particles, both displacement plating and reduction methods may be used, or either one may be used. When both displacement plating and reduction methods are used, they may be used in either order or in reverse order. In particular, using the displacement plating method is preferable because it allows for a nearly uniform distribution of the silver coating layer on the surface of the core particles and suppresses aggregation of the silver particles forming the silver coating layer.

[0054] In the displacement plating method, a dispersion containing core particles is mixed with an aqueous solution containing a silver compound. This causes a displacement reaction between the copper and silver in the core particles in the reaction solution, resulting in the deposition of silver on the surface of the core particles and the formation of silver-coated copper particles with a silver coating layer. As a result, silver-coated copper powder consisting of aggregates of silver-coated copper particles is obtained.

[0055] A silver compound-containing aqueous solution can be prepared by mixing a silver compound source with water. Commonly used silver salts can be used as the source of the silver compound. Specifically, examples include, but are not limited to, silver salts such as silver nitrate, silver oxide, silver sulfate, silver acetate, and silver carbonate. One or more types of silver compound sources can be used. From the viewpoint of successfully obtaining silver-coated copper powder, it is preferable that the silver compound source contains at least silver nitrate.

[0056] There are no particular restrictions on the method of mixing the silver compound source with water. For example, one method is to stir the water and then add the silver compound source and mix. When using two or more types of silver compound sources in combination, they may be added simultaneously or sequentially.

[0057] In the process of obtaining silver-coated copper particles, an aqueous solution containing a silver compound is added to the dispersion. This generates silver-coated copper particles in the reaction solution, in which a silver coating layer is formed on at least a portion of the surface of the core particles. This process is preferably carried out while stirring the reaction solution. If the core particles aggregate when the silver coating layer is formed, multiple silver-coated copper particles will form clumps bound together via silver. Stirring the reaction solution can suppress the settling and aggregation of core particles, and silver-coated copper particles can be successfully obtained. It is preferable to continue stirring the reaction solution until the formation of the silver coating layer by the silver substitution plating reaction is complete. There are no particular restrictions on the method of stirring the reaction solution; for example, it is common to use a stirring blade, but known methods can be used. The reaction solution may be stirred continuously or intermittently.

[0058] In the process of obtaining silver-coated copper particles, it is preferable to add a quantitative amount of an aqueous solution containing a silver compound to the dispersion. If an excess amount of silver ions is present in the reaction solution, the silver coating layer formed on the surface of the core particles will segregate. By adding a quantitative amount of the aqueous solution containing a silver compound, an excessive increase in the concentration of silver ions in the reaction solution can be suppressed, and the silver coating layer can be formed almost uniformly. From the viewpoint of making these advantages even more pronounced, in this process, it is preferable to add the aqueous solution containing a silver compound so that silver ions are added at a rate of 0.01 g / (L·min) or more per 100 g / L of core particles in the dispersion, more preferably 0.03 g / (L·min) or more, and even more preferably 0.05 g / (L·min) or more. From a similar viewpoint, it is preferable to add the aqueous solution containing a silver compound so that silver ions are added at a rate of 1.00 g / (L·min) or less per 100 g / L of core particles in the dispersion, more preferably 0.90 g / (L·min) or less, and even more preferably 0.80 g / (L·min) or less.

[0059] In the process of obtaining silver-coated copper particles, it is preferable to maintain the concentration of silver ions in the reaction solution within a predetermined range while the silver coating layer is being formed. Specifically, from the viewpoint of forming a more uniform silver coating layer, it is preferable to maintain the concentration of silver ions in the reaction solution at 0.001 mol / L or higher, more preferably at 0.003 mol / L or higher, and even more preferably at 0.005 mol / L or higher. From a similar viewpoint, it is preferable to maintain the concentration of silver ions in the reaction solution at 0.15 mol / L or lower, more preferably at 0.14 mol / L or lower, and even more preferably at 0.13 mol / L or lower. The concentration of silver ions in the reaction solution can be adjusted, for example, by adjusting the concentration of silver ions in an aqueous solution containing a silver compound, or by adjusting the rate at which the aqueous solution containing a silver compound is added to the dispersion. Specifically, by adding an aqueous solution containing a silver compound to the dispersion in a fixed amount and appropriately adjusting the rate at which the aqueous solution is added in accordance with the concentration of silver ions in the reaction solution, the concentration of silver ions in the reaction solution can be controlled to the above-mentioned range.

[0060] Furthermore, in the process of obtaining silver-coated copper particles, it is preferable to maintain the pH of the reaction solution within a predetermined range while the silver coating layer is being formed. Specifically, from the viewpoint of forming a more uniform silver coating layer, it is preferable to maintain the pH of the reaction solution at 1.0 or higher, more preferably at 1.2 or higher, and even more preferably at 1.5 or higher. From a similar viewpoint, it is preferable to maintain the pH of the reaction solution at 8.0 or lower, more preferably at 7.5 or lower, and even more preferably at 7.0 or lower. The pH of the reaction solution can be adjusted, for example, by adding a pH adjusting agent to the dispersion. Specifically, as the formation of the silver coating layer progresses by adding the silver compound-containing aqueous solution, the pH of the dispersion decreases, and by adding a pH adjusting agent, the pH of the reaction solution can be controlled to the aforementioned range. As a pH adjusting agent, for example, a complexing agent such as ethylenediaminetetraacetic acid or its salt, as described later, can be used.

[0061] The addition of the silver compound-containing aqueous solution to the dispersion may be quantitatively carried out over the entire time the silver compound-containing aqueous solution is added, or it may be quantitatively carried out only during a predetermined time period within that time. In the latter case, the amount of silver compound-containing aqueous solution added to the dispersion may be increased or decreased at arbitrary intervals during other time periods. In the latter case, from the viewpoint of suppressing an excessive increase in the concentration of silver ions in the reaction solution and forming a substantially uniform silver coating layer, the time for quantitatively adding the aqueous solution containing the silver compound is preferably 30% or more, more preferably 35% or more, and even more preferably 40% or more, of the total time for adding the aqueous solution. From a similar viewpoint, the time for quantitatively adding the aqueous solution containing the silver compound is preferably 100% or less, more preferably 95% or less, and even more preferably 90% or less, of the total time for adding the aqueous solution.

[0062] The addition of the silver compound-containing aqueous solution to the dispersion may be continuous or intermittent. When the silver compound-containing aqueous solution is added intermittently, the period during which the silver compound-containing aqueous solution is not added can be set to a short enough time that it can be considered as if the silver compound-containing aqueous solution were being added continuously. From the viewpoint of forming a substantially uniform silver coating layer on the surface of the core particles, it is preferable to add the silver compound-containing aqueous solution continuously. In the process of obtaining silver-coated copper particles, it is preferable to set the addition time of the silver compound-containing aqueous solution within a predetermined range. This makes it easier to suppress an excessive increase in the concentration of silver ions in the reaction solution and to form a substantially uniform silver coating layer. From the viewpoint of making these advantages even more pronounced, in this process, it is preferable to add the silver compound-containing aqueous solution to the dispersion over a period of 15 minutes or more, more preferably 20 minutes or more, and even more preferably 25 minutes or more. From a similar viewpoint, it is preferable to add the silver compound-containing aqueous solution to the dispersion over a period of 120 minutes or less, more preferably 100 minutes or less, and even more preferably 80 minutes or less. When the silver compound-containing aqueous solution is added intermittently, the "addition time" referred to here means the total addition time of the silver compound-containing aqueous solution.

[0063] In the process of obtaining silver-coated copper particles, it is preferable to add a complexing agent to the reaction solution. To form a nearly uniform silver coating layer on the surface of core particles, it is preferable to control the reaction rate and carry out the formation at a constant rate. On the other hand, if copper ions and other by-products from the substitution reaction between copper and silver ions reprecipitate, and copper hydroxides and oxides are formed on the surface of the core particles, the reaction rate will fluctuate, and the ability to form the silver coating layer will decrease. The inventors of this invention have diligently studied how to improve this point and have found that by using a complexing agent in the process of obtaining silver-coated copper particles, a complex can be formed with copper ions in the reaction solution, thereby suppressing the decrease in the ability to form the silver coating layer. Furthermore, they have also found that by forming complexes with copper ions and silver ions, the reaction rate of silver coating layer formation can be effectively controlled. From the viewpoint of further enhancing the advantages mentioned above, it is preferable to use a complexing agent with a high complex stability constant with respect to copper and silver ions. Since the core particles are mainly composed of copper, it is particularly preferable to select a complexing agent with consideration to its complex stability constant with copper. Specifically, examples of complexing agents include those selected from the group consisting of ethylenediaminetetraacetic acid (EDTA), iminodiacetic acid, diethylenetriamine, triethylenediamine, and salts thereof. One or more complexing agents can be used. From the viewpoint of suppressing a decrease in the ability to form a silver coating layer and effectively controlling the reaction rate of silver coating layer formation, EDTA is preferred as the complexing agent. However, as mentioned above, the complexing agent can also be used to adjust the pH of the dispersion. In this case, the complexing agent used for pH adjustment and the complexing agent used to suppress the decrease in the ability to form the silver coating layer and to control the reaction rate of silver coating layer formation may be the same or different.

[0064] In the process of obtaining silver-coated copper particles, it is preferable that the complexing agent is already present in the reaction solution when the silver coating layer is formed on the surface of the core particles. This is because it is possible to form complexes with copper and silver ions without delay after the re-deposition of these ions, thereby preventing interference with the formation of the silver coating layer and effectively controlling the reaction rate of the silver coating layer formation. From the viewpoint of forming a uniform coating layer, it is preferable to add the complexing agent in multiple stages in this process. Therefore, it is preferable to add the complexing agent in at least two stages: before adding the silver compound-containing aqueous solution to the dispersion, and during the addition of the silver compound-containing aqueous solution to the dispersion. In the former case, the complexing agent can be added all at once to the dispersion, and in the latter case, it can be added sequentially to the reaction solution. In the latter case, it can also be added at any time after the formation of silver-coated copper particles in the reaction solution has begun. From the viewpoint of making the above-mentioned effects even more pronounced, it is preferable to add the complexing agent after adding half the amount of the silver compound-containing aqueous solution to the dispersion. A positive correlation exists between the amount of silver ions precipitated and the concentration of copper ions eluted into the reaction solution. Furthermore, a positive correlation also exists between the amount of silver compound-containing aqueous solution added and the amount of silver precipitated. Therefore, as described above, by determining the amount and timing of complexing agent addition based on the amount of silver compound-containing aqueous solution added, a complex with the copper ion complexing agent can be formed more effectively. The complexing agent can be added at any time during any operation until the process of obtaining silver-coated copper particles is completed. For example, the complexing agent may be added to the dispersion, or to the aqueous solution containing the silver compound. The addition of the complexing agent may be carried out continuously or intermittently, as long as it is done in at least two separate additions. When adding the complexing agent from the second addition onward, the complexing agent may be added to the reaction solution all at once, or it may be added sequentially.

[0065] When adding the complexing agent for the first time, from the viewpoint of not hindering the formation of the silver coating layer and effectively controlling the reaction rate of silver coating layer formation, it is preferable to add the complexing agent in an equivalent ratio of 0.2 or more relative to the added silver ions, more preferably 0.3 or more, and even more preferably 0.4 or more. From a similar viewpoint, it is preferable to add the complexing agent in an equivalent ratio of 1.0 or less relative to the added silver ions, more preferably 0.9 or less, and even more preferably 0.8 or less. In this specification, 1 equivalent of complexing agent refers to the number of moles of complexing agent that form a complex with 1 mole of silver ions. When adding the complexing agent for the second time or later, from the viewpoint of achieving both the formation of the silver coating layer not being hindered and the effective control of the reaction rate of silver coating layer formation, and forming a uniform coating layer, it is preferable to add the complexing agent in an equivalent ratio of 0.2 or more relative to the added silver ions, more preferably 0.3 or more, and even more preferably 0.4 or more. From the same viewpoint, it is preferable to add the complexing agent in an equivalent ratio of 1.0 or less relative to the added silver ions, more preferably 0.9 or less, and even more preferably 0.8 or less.

[0066] From the viewpoint of achieving both unimpeded formation of the silver coating layer and effective control of the reaction rate of silver coating layer formation, and forming a uniform coating layer, the complexing agent may be added in two or more separate additions, or even three or more separate additions. When adding the complexing agent from the second addition onward, it can be added at any time after silver-coated copper particles have begun to form in the reaction solution. For example, the complexing agent can be added after half the amount of the silver compound-containing aqueous solution has been added to the dispersion. In this specification, the addition made at least 5 seconds after the nth addition has been stopped is considered the (n+1)th addition (where n is a natural number greater than or equal to 2). From the viewpoint of further enhancing the above-mentioned advantages, the number of additions may be 10 or less, but 2 additions are particularly preferred.

[0067] Once silver-coated copper particles are obtained, they are washed with water, and then the reaction solution is separated into solid and liquid components using a centrifuge, Nutsch, and filter press to separate and recover the silver-coated copper particles from the reaction solution. In the process described later, it is preferable to thoroughly wash the silver-coated copper particles with water from the viewpoint of forming a highly uniform surface treatment layer on the surface of the silver-coated copper particles. Whether the washing is sufficient can be evaluated by the conductivity of the washing solution after washing the silver-coated copper particles. Specifically, the conductivity of the washing solution after washing the silver-coated copper particles is preferably 100 μS / m or less, more preferably 50 μS / m or less, and even more preferably 10 μS / m or less. The separated silver-coated copper particles may be dried before use in the next process. The method for washing the silver-coated copper particles with water is not particularly limited. For example, a method of filtering the slurry by suction filtration with a Nütsch filter and then filtration washing with pure water, a method of repeatedly decanting and diluting with pure water, or a method of separating the solid-liquid, reslurrying with pure water, and then repeating the solid-liquid separation again can be employed.

[0068] Next, a surface treatment agent is applied to the surface of the silver-coated copper particles to form a surface treatment layer. The surface treatment agent described above can be used as the surface treatment agent.

[0069] From the viewpoint of successfully obtaining the desired silver-coated copper powder, it is preferable to apply the surface treatment agent so as to treat the entire surface of the silver-coated copper particles. From this viewpoint, it is preferable to employ a method of immersing the silver-coated copper particles in a liquid containing the surface treatment agent in the process of applying the surface treatment agent. Specifically, examples include a method in which the silver-coated copper particles are immersed in a funnel into which the liquid is introduced, and then the treated silver-coated copper particles are removed by vacuum filtration, and a method in which the silver-coated copper particles are immersed in a reaction vessel into which the liquid is introduced, and then the treated silver-coated copper particles are recovered by decantation. The solvent for the liquid is not particularly limited as long as it can dissolve the surface treatment agent, and for example, water, ethanol, 2-propanol, acetone, toluene, butanol, and terpineol can be used. Once the surface treatment is complete, the silver-coated copper particles are dried to obtain silver-coated copper powder consisting of aggregates of these silver-coated copper particles.

[0070] The silver-coated copper powder of the present invention can be used in the form of a conductive resin composition by mixing it with a thermosetting resin. The conductive resin composition comprises at least the silver-coated copper powder and thermosetting resin of the present invention. Examples of thermosetting resins include acrylic resins, epoxy resins, ethyl cellulose, and carboxyethyl cellulose.

[0071] In addition to the silver-coated copper powder and thermosetting resin of the present invention, the conductive resin composition may also contain at least one of an organic solvent, a dispersant, and glass frit. As organic solvents, those similar to those previously used in the field of conductive resin compositions containing metal powders can be used without particular limitations. Examples of such organic solvents include monohydric alcohols such as terpineol and dihydroterpineol; polyhydric alcohols; polyhydric alcohol alkyl ethers such as ethyl carbitol and butyl carbitol; polyhydric alcohol aryl ethers; polyethers; esters such as carbitol acetate, butyl cellosolve acetate, and butyl carbitol acetate; nitrogen-containing heterocyclic compounds; amides; amines, and saturated hydrocarbons. These organic solvents can be used individually or in combination of two or more. From the viewpoint of having a high reducing effect and suppressing unintended oxidation of silver-coated copper powder during sintering, it is preferable to use polyethers such as polyethylene glycol and polypropylene glycol. From a similar viewpoint, when polyethylene glycol is used as the organic solvent, its number average molecular weight is preferably 120 to 400, and more preferably 180 to 400. Examples of dispersants include nonionic surfactants that do not contain sodium, calcium, phosphorus, sulfur, and chlorine. Examples of glass frits include borosilicate glass, barium borosilicate glass, and zinc borosilicate glass. These can be used individually or in combination of two or more.

[0072] The above-described conductive resin composition can be applied to a substrate to form a coating film, which can then be heat-cured to form a cured body of silver-coated copper powder. The cured body is suitably used, for example, for forming various electrodes in solar cells, forming circuits on printed circuit boards, and ensuring electrical conductivity of external electrodes in multilayer ceramic capacitors. Examples of printed circuit boards include those made of glass epoxy resin, flexible printed circuit boards made of polyimide, etc., depending on the type of electronic circuit in which the copper powder is used.

[0073] The content of silver-coated copper powder and organic solvent in the conductive resin composition can be appropriately set according to the specific application and application method of the conductive resin composition, but is preferably 5% by mass or more and 95% by mass or less, and more preferably 80% by mass or more and 90% by mass or less.

[0074] The conductive resin composition can be applied by methods such as inkjet printing, dispenser printing, microdispenser printing, gravure printing, screen printing, dip coating, spin coating, spray coating, bar coating, and roll coating.

[0075] The curing temperature of the coating film can be, for example, 100°C to 250°C. Curing can be carried out, for example, under an oxidizing atmosphere or a non-oxidizing atmosphere. An oxidizing atmosphere is, for example, an oxygen-containing atmosphere. A non-oxidizing atmosphere is, for example, a reducing atmosphere such as hydrogen and carbon monoxide, a weakly reducing atmosphere such as a hydrogen-nitrogen mixed atmosphere, and an inert atmosphere such as argon, neon, helium and nitrogen. In any atmosphere, the curing time is preferably 10 minutes to 3 hours, and more preferably 30 hours to 2 hours, provided that the temperature is within the above-mentioned temperature range.

[0076] The above embodiments of the present invention encompass the following technical concepts. [1] Core particles containing copper, Displaced on the surface of the core particles, a coating layer containing silver, Displaced on the surface of the coating layer, a surface treatment layer containing a surface treatment agent, A method for evaluating the uniformity of the coating layer in silver-coated copper powder containing the following: An observation area is defined in the silver-coated copper powder, and multiple irradiation areas are provided within the observation area to irradiate it with excitation laser light of a wavelength absorbable by the silver element. By irradiating each of the irradiation regions with the laser light, the Raman spectrum of the silver-coated copper powder is obtained for each irradiation region. A plurality of normalized Raman spectra are obtained by normalizing each of the Raman spectra acquired for each of the irradiation regions with respect to the peak intensity of a reference peak derived from copper oxide, selecting one wavenumber of the peak derived from the surface treatment agent, which is observed in the plurality of normalized Raman spectra, calculating a ratio n / N of the number n of the irradiation regions where the intensity of the normalized Raman spectrum at the wavenumber is equal to or greater than a threshold value, to the total number N of the irradiation regions, and evaluating the uniformity of the coating layer based on the ratio, the method for evaluating the uniformity of a coating layer. [2] The evaluation method according to [1], wherein the wavelength of the excitation laser light is 325 nm or more and 1064 nm or less. [3] The evaluation method according to [1] or [2], wherein the reference peak is a peak observed at a wavenumber of 245 cm -1 or more and 255 cm -1 or less. [4] A silver-coated copper powder comprising: core particles containing copper; a coating layer disposed on surfaces of the core particles and containing silver; and a surface treatment layer disposed on a surface of the coating layer and containing a surface treatment agent, wherein a ratio n / N of n to N calculated by the following method is 0.05 or more. <Calculation method of n / N> An observation region is defined on the silver-coated copper powder, and a plurality of irradiation regions to be irradiated with excitation laser light having a wavelength of 532 nm are provided in the observation region, the laser light is irradiated to each of the irradiation regions, whereby a Raman spectrum of the silver-coated copper powder is acquired for each of the irradiation regions, A plurality of normalized Raman spectra are obtained by normalizing each of the Raman spectra acquired for each of the irradiation regions with respect to the peak intensity of a reference peak observed at a wavenumber of 245 cm -1 or more and 255 cm -1 or less, one wavenumber of the peak derived from the surface treatment agent, which is observed in the plurality of normalized Raman spectra, is selected, determining the number n of the irradiation regions where the intensity of the normalized Raman spectrum at the wavenumber is 10 times or more the peak intensity of the reference peak, calculating the ratio n / N of n to the total number N of the irradiation regions. [5] The silver-coated copper powder according to [4], which has a volume cumulative particle diameter D at a cumulative volume of 50 vol% as measured by a laser diffraction scattering particle size distribution measurement method 50 of 1.0 μm or more and 10.0 μm or less. [6] The silver-coated copper powder according to [4] or [5], which has a BET specific surface area of 0.08 m 2 / g or more and 1.50 m 2 / g or less. [7] The silver-coated copper powder according to any one of [4] to [6], which has an oxygen increase rate of 150.0% or less. [8] The silver-coated copper powder according to any one of [4] to [7], wherein the surface treatment layer contains at least one selected from fatty acids and azole compounds. [9] A conductive resin composition comprising a thermosetting resin and the silver-coated copper powder according to any one of [4] to [8].

[10] Silver-coated copper powder comprising core particles containing copper, and a coating layer disposed on the surface of the core particles and containing silver, wherein the ratio n / N of n to N calculated by the following method is 0.05 or more. <Method for calculating n / N> forming a surface treatment layer containing a surface treatment agent on the surface of the coating layer, defining an observation region on the silver-coated copper powder, and providing a plurality of irradiation regions in the observation region, each of which is irradiated with excitation laser light having a wavelength of 532 nm, irradiating each of the irradiation regions with the laser light to obtain a Raman spectrum of the silver-coated copper powder for each of the irradiation regions, normalizing each of the Raman spectra obtained for each irradiation region with respect to the peak intensity of a reference peak observed at a wavenumber of 245 cm -1 to 255 cm -1 thereby obtaining a plurality of normalized Raman spectra, One wavenumber of the peak originating from the surface treatment agent observed in the above-mentioned multiple normalized Raman spectra is selected, The number n of irradiation regions is determined such that the intensity of the normalized Raman spectrum at the wavenumber is 10 times or more the peak intensity of the reference peak. Calculate the ratio n / N to the total number N of irradiation regions. [Examples]

[0077] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to these examples. Unless otherwise specified, "%" means "mass%".

[0078] [Examples 1-8] As core particles, we prepared MA-C series atomized copper particles manufactured by Mitsui Mining & Smelting Co., Ltd. The average particle size of the core particles used in each example is shown in Table 1 below. Core particles were added to pure water kept at 40°C in a 10 L reaction vessel and thoroughly stirred to prepare a dispersion. The content of core particles in the dispersion was as shown in Table 1. Separately, silver nitrate was added to pure water to prepare an aqueous solution containing a silver compound with a silver ion concentration of 0.5 mol / L. 28 g of EDTA was added all at once to 5 L of dispersion as a complexing agent and thoroughly stirred. While stirring this dispersion, an aqueous solution containing a silver compound was continuously added to generate silver-coated copper particles in the reaction solution. The addition time of the aqueous solution containing the silver compound and the total amount of silver added relative to the core particles are shown in Table 1. The aqueous solution containing the silver compound was added quantitatively throughout the entire addition time. 30 minutes after the start of addition of the aqueous solution containing the silver compound, aqueous EDTA was added sequentially to maintain the pH of the reaction solution at 1.5 to 5.0. The total amount of EDTA added as a complexing agent is shown in Table 1. Using a Nutsch sieve, the reaction solution was suction-filtered until its conductivity reached the values ​​shown in Table 1, followed by solid-liquid separation by filtration. 0.5 g of the surface treatment agent shown in Table 1 was added to 1 L of acetone and thoroughly stirred to prepare a solution containing the treatment agent. 1 L of this solution was added to the Nutsch sieve to immerse the silver-coated copper particles, thereby applying the surface treatment agent to the silver-coated copper particles. The treated silver-coated copper particles were removed by vacuum filtration and dried at 70°C for 5 hours. In this way, silver-coated copper powder consisting of aggregates of silver-coated copper particles was obtained. In Table 1, "BTA" represents benzotriazole.

[0079] [Comparative Example 1] Before adding the aqueous solution containing the silver compound, the entire amount of the EDTA aqueous solution, which is the complexing agent of the dispersion, was added. No further complexing agent was added after the aqueous solution containing the silver compound was added. Stearic acid was used as a surface treatment agent. Silver-coated copper powder was produced in the same manner as in Example 1, except for the points mentioned above. [Comparative Example 2] Silver-coated copper powder was manufactured in the same manner as in Example 1, except that the silver-coated copper particles were not subjected to surface treatment.

[0080] [Evaluation of the uniformity of the coating layer] 50 mg of silver-coated copper powder prepared in each example and comparative example was placed on a glass slide, and the top surface of the silver-coated copper powder was smoothed as much as possible using a coverslip or the tip of a microspatula. Next, an observation area for the excitation laser light was defined for this silver-coated copper powder. The observation area was a 20 μm × 20 μm square. 400 irradiation areas were set within this observation area. Each irradiation area was a circle with a diameter of 0.8 μm and was set up in a 20 × 20 grid. The spacing between adjacent irradiation areas was 0.4 μm in both the vertical and the horizontal directions perpendicular to it. Next, the Raman spectra of the silver-coated copper powder were obtained for each irradiation region by sequentially irradiating each of the irradiation regions with excitation laser light. The Raman spectrum measurement conditions were as follows. In addition, the Raman spectrum of a standard sample, Si, was measured separately, and the wavenumber of the main peak of this standard sample was 520.5 cm⁻¹. -1To achieve this, wavenumber calibration was performed on the Raman spectra of each irradiation region. • Device: Invia Qontor (manufactured by Renishaw Corporation) ·Light source: 532nm (RL532-08 150mW) • Objective lens: 100x • Grating: 1800mm / L • Irradiation time: 10 seconds • Number of times accumulated: 1 • Slit width: 65 μm • Laser power: 0.1% • Laser output: 0.13mW ·Using Livetrack function

[0081] Each obtained Raman spectrum was subjected to baseline correction (intelligence polynomial: order 6) within Renishaw's WiRE 5.6. Subsequently, it was measured at 250 ± 5 cm. -1 Normalized Raman spectra (400 in total) were obtained for each irradiation region by normalizing the peak intensity relative to the reference peak observed. Normalization was performed so that the peak intensity of the reference peak became 1. One wavenumber was selected from the peaks originating from the surface treatment agent observed in the normalized Raman spectrum (the selected wavenumber is shown in Table 1), and the percentage of the irradiated region where the intensity at that wavenumber was 10 or greater (n / N as described above) was calculated. The results are shown in Table 1.

[0082] [Average particle size] Using an automated sample feeder for laser diffraction particle size distribution analyzers (Microtrac SDC, manufactured by Microtrac-Bell Corporation), silver-coated copper powder was mixed with two drops of pure water containing 0.1% polyoxyethylene octylphenyl ether. This pure water was then added to a 0.1% aqueous solution of SN Dispersant 5468, manufactured by Sunopco. After irradiating this aqueous solution with 40W ultrasound for 5 minutes, the particle size distribution was measured using a Microtrac-Bell MT3300EX II laser diffraction particle size distribution analyzer, and the average particle size was measured from the resulting volume-based particle size distribution chart. When measuring the average particle size, the flow velocity was set to 65%, the solvent refractive index to 1.33, the particle permeability condition to "reflection", the measurement range to 0.122 μm or more and 704.0 μm or less, and the measurement time to 30 seconds.

[0083] [Measurement of BET specific surface area] The BET specific surface area of ​​the silver-coated copper powders in the examples and comparative examples was measured using the BET single-point method with a MacSorb manufactured by Mountec Co., Ltd. The results are shown in Table 1.

[0084] [Measurement of oxygen elevation rate] The oxygen elevation rate O was measured by determining the difference between the initial oxygen concentration and the oxygen concentration after holding the sample (silver-coated copper powder) in a high-temperature humidifier at 85°C and 85% RH for 200 hours and then cooling it to room temperature. Specifically, the oxygen elevation rate was calculated by subtracting the initial oxygen concentration from the oxygen concentration after 200 hours and dividing by the initial oxygen concentration. The oxygen concentration was measured using the following method. Specifically, silver-plated copper powder was placed in a graphite crucible and heated and melted in a He atmosphere using an EMGA-820ST manufactured by Horiba, Ltd. The resulting carbon monoxide (carbon dioxide) was measured by non-dispersive infrared absorption spectroscopy to determine the oxygen concentration (mass%). The results are shown in Table 1. Table 1 also shows the oxygen elevation rate O divided by the BET specific surface area SSA (O / SSA). A smaller O / SSA value indicates that the silver-coated copper powder is less susceptible to oxidation (i.e., the coating layer is more uniformly distributed).

[0085] [Measurement of surface treatment agent content] The content of surface treatment agents in silver-coated copper powder was measured by substituting it with the carbon content. Specifically, the carbon content was measured using a carbon-sulfur analyzer (CS844, manufactured by LECO Japan LLC). 0.50 g of copper powder was placed in a magnetic crucible, and oxygen gas (purity: 99.5 vol%) was used as the carrier gas. The analysis time was 40 seconds. The results are shown in Table 1.

[0086] [Table 1]

[0087] As is clear from Table 1, the silver-coated copper powders of each example have a lower O / SSA value and a more uniform coating layer than the silver-coated copper powders of each comparative example. Furthermore, the 1390 cm calculated in each example -1 The percentage n / N of the irradiated area with an intensity of 10 or higher was higher than the percentage calculated in Comparative Example 1, which used copper powder with low uniformity of the coating layer. Therefore, it can be seen that the uniformity of the coating layer can be easily evaluated based on the percentage n / N. In Comparative Example 2, which does not have a surface treatment layer, the silver-coated copper powder was 1390 cm². -1 No peaks with this wavenumber were observed. [Explanation of symbols]

[0088] 1. Laser light 2 Silver coated copper powder 3 electric field 4,6 Raman scattering 5 areas

Claims

1. Copper-containing core particles, Displaced on the surface of the core particles, a coating layer containing silver, Displaced on the surface of the coating layer, a surface treatment layer containing a surface treatment agent, A method for evaluating the uniformity of the coating layer in silver-coated copper powder containing the following: An observation area is defined in the silver-coated copper powder, and multiple irradiation areas are provided within the observation area to irradiate it with excitation laser light of a wavelength absorbable by the silver element. By irradiating each of the irradiation regions with the laser light, the Raman spectrum of the silver-coated copper powder is obtained for each irradiation region. By normalizing each of the Raman spectra obtained for each irradiation region with respect to the peak intensity of a reference peak, multiple normalized Raman spectra are obtained. One wavenumber of the peak originating from the surface treatment agent observed in the aforementioned multiple normalized Raman spectra is selected, The ratio n / N of the number of irradiation regions where the intensity of the normalized Raman spectrum at the wavenumber is equal to or greater than a threshold is calculated relative to the total number N of irradiation regions. A method for evaluating the uniformity of a coating layer, wherein the uniformity of the coating layer is evaluated based on the aforementioned ratio.

2. The evaluation method according to claim 1, wherein the wavelength of the excitation laser light is 325 nm or more and 1064 nm or less.

3. The aforementioned reference peak is 245 cm. -1 Over 255cm -1 The evaluation method according to claim 1 or 2, wherein the peak observed is at the following wavenumbers.

4. Copper-containing core particles, Displaced on the surface of the core particles, a coating layer containing silver, Displaced on the surface of the coating layer, a surface treatment layer containing a surface treatment agent, Silver-coated copper powder containing the following, wherein the ratio of n to N, n / N, calculated by the following method, is 0.05 or more. <How to calculate n / N> An observation area is defined in the silver-coated copper powder, and multiple irradiation areas are provided within the observation area to irradiate it with excitation laser light with a wavelength of 532 nm. By irradiating each of the irradiation regions with the laser light, the Raman spectrum of the silver-coated copper powder is obtained for each irradiation region. Each of the Raman spectra acquired for each of the irradiation regions was processed at 245 cm². -1 Over 255cm -1 By normalizing the peak intensity of the reference peak observed at the following wavenumbers, multiple normalized Raman spectra are obtained. One wavenumber of the peak originating from the surface treatment agent observed in the aforementioned multiple normalized Raman spectra is selected, The number n of irradiation regions is determined such that the intensity of the normalized Raman spectrum at the wavenumber is 10 times or more the peak intensity of the reference peak. Calculate the ratio n / N to the total number N of irradiation regions.

5. Volume cumulative particle size D at 50% cumulative volume, as measured by laser diffraction scattering particle size distribution analysis. 50 The silver-coated copper powder according to claim 4, wherein the particle size is 1.0 μm or more and 10.0 μm or less.

6. BET specific surface area is 0.08 m² 2 / g or more 1.50m 2 The silver-coated copper powder according to claim 4, wherein the amount is less than or equal to / g.

7. The silver-coated copper powder according to claim 4, wherein the oxygen elevation rate is 150.0% or less.

8. The silver-coated copper powder according to claim 4, wherein the surface treatment layer comprises at least one selected from fatty acids and azole compounds.

9. A conductive resin composition comprising a thermosetting resin and the silver-coated copper powder described in claim 4.

10. Copper-containing core particles, Displaced on the surface of the core particles, a coating layer containing silver, Silver-coated copper powder containing the following, wherein the ratio of n to N, n / N, calculated by the following method, is 0.05 or more. <How to calculate n / N> A surface treatment layer containing a surface treatment agent is formed on the surface of the coating layer. An observation area is defined in the silver-coated copper powder, and multiple irradiation areas are provided within the observation area to irradiate it with excitation laser light with a wavelength of 532 nm. By irradiating each of the irradiation regions with the laser light, the Raman spectrum of the silver-coated copper powder is obtained for each irradiation region. each of the Raman spectra acquired for each of the aforementioned irradiation regions is 245 cm -1 to 255 cm -1 normalized against the peak intensity of a reference peak observed at a wavenumber equal to or less than the aforementioned value, so as to acquire a plurality of normalized Raman spectra, One wavenumber of the peak originating from the surface treatment agent observed in the aforementioned multiple normalized Raman spectra is selected, The number n of irradiation regions is determined such that the intensity of the normalized Raman spectrum at the wavenumber is 10 times or more the peak intensity of the reference peak. Calculate the ratio n / N to the total number N of irradiation regions.

Citation Information

Patent Citations

  • Silver-coated metal powder and method for producing the same, and electroconductive coating material

    JP2021055142A